2012
DOI: 10.1016/j.jbtep.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive therapy for body dysmorphic disorder patients in Iran: Acceptability and proof of concept

Abstract: The purpose of the present study was to determine the effect of metacognitive therapy (MCT) on symptoms of body dysmorphic disorder (BDD) and on symptoms of thought-fusion, by means of a wait-list controlled clinical trial. Participants were referred from dermatology and cosmetic surgery clinics in the city of Isfahan, Iran, and 20 patients were selected on the basis of DSM-IV-TR diagnostic criteria for BDD. They were randomly assigned to either the experimental or the wait-list control group. The Yale-Brown O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 21 publications
(26 reference statements)
6
48
2
2
Order By: Relevance
“…As predicted by model of the study, researchers have consistently found that BDD is characterized by a heightened subjective experience of worry as an uncontrollable process and any efforts at control prove futile and unproductive. Despite their acknowledged inability to control worry, it is interesting that individuals with BDD are highly invested in continuing with their efforts toward gaining control over worry and unwanted repetitive thoughts [4] [5] [9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As predicted by model of the study, researchers have consistently found that BDD is characterized by a heightened subjective experience of worry as an uncontrollable process and any efforts at control prove futile and unproductive. Despite their acknowledged inability to control worry, it is interesting that individuals with BDD are highly invested in continuing with their efforts toward gaining control over worry and unwanted repetitive thoughts [4] [5] [9].…”
Section: Discussionmentioning
confidence: 99%
“…It assesses BDD-related preoccupations, repetitive behaviors, insight, and avoidance. The reliability and validity of the BDD-YBOCS Farsi version version was demonstrated by Rabiei et al [4] in both healthy and clinical samples. The alpha coefficients ranged from 0.78 to 0.93 for the BDD-YBOCS total score and for its subscales (preoccupations, repetitive behaviors).…”
Section: Yale-brown Obsessive Compulsive Scale Modified For Body Dysmmentioning
confidence: 91%
See 3 more Smart Citations